Model analysis: A quantum approach to analyze understanding - Pornrat Wattanakasiwich (2018)
The objective of this study had two folds-1) investigating students' basic understanding of force and motion and 2) employing a new analysis method, called model analysis. This method helps obtain students' alternative knowledge and probabilities for students to use such knowledge in a range of equivalent contexts. The model analysis consists of two algorithmsconcentration factor and model estimation. The data were student responses on Force and Motion Conceptual Evaluation (FMCE). 545 engineering freshmen taking an introductory physics with calculus at Chiang Mai University took both pre- and post-test. The concentration factor indicated that students had misconception in concepts of Newton's laws. Hence the class model density matrices for both pre/post scores were constructed to determine characteristics of the pre/post class; eigenvalues and eigenvectors were calculated by the eigenvalue decomposition method. Results from model plots suggested that most students still had misconception about force-motion concept and had mixed model states about Newton's third law.